Knowledge of tuberculosis among physicians working at community health stations in Vietnam - Ly, Tran Thi; Hoa, Nguyen Phuong; Nguyet, Nguyen Thi; Thuy, Hoang Thu; Giang, Pham Ngan (International Journal of Public Health Science (IJPHS), 2024)
Tuberculosis (TB) remains a significant health problem worldwide, including in Vietnam, where around 174,000 newly diagnosed cases and 13,200 patients died in 2018. There are challenges in the diagnostic process, treatment, and follow-up. The physicians with knowledge of TB working at commune health stations play an essential role in this struggle. The primary purpose of this study was to evaluate knowledge of TB and related factors among physicians working at community health stations in the Northern provinces of Vietnam. A cross-sectional survey was implemented on 335 physicians working at community health stations in 5 Northern provinces in Vietnam from September 2019 to October 2020. The result showed that the TB knowledge of physicians was not good. There were some severe knowledge gaps concerning at-risk groups, the main symptoms of TB, sputum tests for both diagnosis and follow-up and management of attack therapy. The TB training participants had better TB knowledge than others (aOR=1.68; 95%CI: 1.047-2.712). This study underlines the importance of clinical experience and TB training to TB knowledge. We suggest that a TB training plan is required for physicians. Our survey results could inform the process of defining the physicians who work at community health stations' role in TB management in the future.